2015
DOI: 10.1016/j.tranon.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Heterogeneity and Permeability of Brain Metastases in Murine Models of HER2-Positive Breast Cancer Through Magnetic Resonance Imaging: Implications for Detection and Therapy

Abstract: OBJECTIVES: Brain metastases due to breast cancer are increasing, and the prognosis is poor. Lack of effective therapy is attributed to heterogeneity of breast cancers and their resulting metastases, as well as impermeability of the blood–brain barrier (BBB), which hinders delivery of therapeutics to the brain. This work investigates three experimental models of HER2 + breast cancer brain metastasis to better understand the inherent heterogeneity of the disease. We use magnetic resonance imaging (MRI) to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…Consistent with previous work [31,46], we demonstrate that changes in passive permeability are independent of lesion size, and do not appear to be related to tumor morphology. Moreover, the observed BTB permeability at different locations within the brain did not appear to influence permeability in these models supporting previous MRI studies examining the distribution of gadolinium-enhancing metastases in similar preclinical models [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous work [31,46], we demonstrate that changes in passive permeability are independent of lesion size, and do not appear to be related to tumor morphology. Moreover, the observed BTB permeability at different locations within the brain did not appear to influence permeability in these models supporting previous MRI studies examining the distribution of gadolinium-enhancing metastases in similar preclinical models [19].…”
Section: Discussionsupporting
confidence: 92%
“…The brain distribution of metastatic foci in each model presented herein appear consistent with similar studies demonstrating more than 50% of metastatic burden occurs in cortical regions, with relatively fewer lesions occurring in the central brain regions, and the least metastatic growth observed in the posterior and olfactory regions [47,48]. Additionally, this work agrees with previous findings [46] suggesting the presence of HER2 does not seem to correlate strongly with changes in vascular permeability (permeability of JIMT-1-BR3, SUM190-BR3, and MDA-MB-231BR-HER2+ lines were not congruent) and that permeability changes appear to be more cell line specific (i.e., MDA-BB-231BR and MDA-MB-231BR-HER2+). Interestingly, Murell et.…”
Section: Discussionsupporting
confidence: 91%
“…Focal therapies with surgical resection and/or radiosurgery can effectively control an individual metastasis, but the risk of developing subsequent brain metastases elsewhere in the brain exceeds 50%, which suggests that integrating these procedures with effective targeted therapies may provide significant clinical benefit (Fife et al, 2004). The successful treatment of brain tumors will need targeted therapies that are: 1) potent against its target, 2) capable of penetrating an intact blood-brain barrier (BBB) replete with efflux transporters (Osswald et al, 2016), and 3) capable of reaching the protected tumor cells that are not clinically detectable upon contrast-enhancing magnetic resonance imaging (Murrell et al, 2015). Many small-molecule molecularly-targeted therapies have limited ability to permeate an intact BBB, which in turn can limit their efficacy against brain tumors (Agarwal et al, 2011;Gampa et al, 2016Gampa et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…208 Recent data suggest that gadolinium-DTPAimpermeable cerebral breast metastases have significantly more proliferative nuclei compared to gadolinium-DTPA-permeable tumors in the mouse brain. 209 In contrast, another study showed that melanoma metastases having a permeable vasculature grow faster than those having an intact BTB. 144 This study also demonstrated that only brain-permeable PI3K inhibitors are active against metastatic lesions, and that targeting micrometastases and even dormant cells is more effective than treating large lesions.…”
Section: Vascularization and The Blood-tumor Barrier Of Metastatic Brmentioning
confidence: 97%